Analisis Penggunaan Financial Technology (Fintech) Syariah Dalam Perspektif Ekonomi Islam - Fazira Salsabila; Putri Mardiyyah Hasibuan; Satria Mariqom Harahap; Purnama Ramadani Silalahi (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to find out how to use Islamic Financial Technology (Fintech) in the perspective of Islamic Economics. This study uses a qualitative method with literature study. The data from this study is data obtained through books, previous research journals, and other literature. This method is used with facts, actual in accordance with existing situations and phenomena. This method is carried out to understand and reveal about the Use of Sharia Financial Technology (Fintech) in the Perspective of Islamic Economics. The results of this study state that sharia financial technology (fintech) must be based on the Koran and Hadith, which are the basic functions for all transactions that comply with Islamic law. According to Islamic teachings originating from the Al-Qur'an and As-Sunnah, all forms of economic and business transactions must respect individual rights and uphold a sense of solidarity with the wider community. The use of Islamic Financial Technology (Fintech) in the Perspective of Islamic Economics is that Islamic Fintech has an Islamic economic foundation and also has a clear and pre-existing legal framework.